2017
DOI: 10.3892/etm.2017.4571
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of carnosine against salsolinol-induced Parkinson's disease

Abstract: Carnosine is a dipeptide of β-alanine and histidine amino acids. It is widely present in muscle and brain tissues. Carnosine has been demonstrated to be an antioxidant agent that is beneficial in animals. Reactive oxygen species (ROS) and aldehydes are are generated from membrane fatty acid oxidation. The antioxidant potential and toxicity of salsolinol had been extensively studied in vivo and in vitro. The present study analyzed the protective effect of carnosine against Parkinson's disease in the salsolinol-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 34 publications
1
20
0
2
Order By: Relevance
“…l-Homocarnosine and l-carnosine were also shown to exert protective effects against DNA damage (Kang 2010), and carnosine supplementation was reported to protect rat brain endothelial cells by scavenging 4-hydroxynonenol and MDA. Moreover, l-carnosine exerted neuroprotective effects in Parkinson's disease (Zhao et al 2017), and both anserine and l-carnosine were shown to exert similar effects in an animal model of focal ischemia.…”
Section: Discussionmentioning
confidence: 96%
“…l-Homocarnosine and l-carnosine were also shown to exert protective effects against DNA damage (Kang 2010), and carnosine supplementation was reported to protect rat brain endothelial cells by scavenging 4-hydroxynonenol and MDA. Moreover, l-carnosine exerted neuroprotective effects in Parkinson's disease (Zhao et al 2017), and both anserine and l-carnosine were shown to exert similar effects in an animal model of focal ischemia.…”
Section: Discussionmentioning
confidence: 96%
“…6, panel a) and superoxide dismutase activity ( Fig. 6, panel b), was significantly reversed following treatment with carnosine, a dipeptide endowed with antioxidant properties (Zhao et al 2017). In addition, catalase activity in brain endothelial cells in salsolinol-treated rats was also significantly reduced (Zhao et al 2017) suggesting that salsolinol may also potentially damage proteins by producing cross-links (Libondi et al 1994;Zhao et al 2017).…”
Section: Ethanol and Tiqsmentioning
confidence: 95%
“…Salsolinol's toxicity has been extensively studied in various in vitro (Yoshikawa 1993;von Bohlen und Halbach et al 2004;Olanow and Tatton 1999) and in vivo (Collins and Neafsey 2002) systems. In particular, in vivo and in vitro studies by Zhao et al (2017) reported that salsolinol could alter rat brain endothelial cells' morphology, but also determine apoptosis and necrosis (Table 1). This cytotoxicity, disclosed in salsolinol-treated rat brain endothelial cells by decreased glutathione content (Fig.…”
Section: Ethanol and Tiqsmentioning
confidence: 99%
See 1 more Smart Citation
“…The robust anti-oxidant, anti-excitotoxic, and mitochondria protecting activities of carnosine mainly rely on its protective effects against oxygen-glucose deprivation and against accumulation of reactive oxygen species (Bae et al, 2013). In a mice model of salsolinol-induced neurotoxicity, carnosine was shown to decrease the MDA and restore the activity of Glutathione(GSH), Superoxide dismutase (SOD) and catalase along with the reduced apoptosis and Reactive Oxygen Species (ROS) production, suggesting its therapeutic effect in salsolinol-induced Parkinson's disease (PD) (Zhao et al, 2017). In summary, an increasing number of studies have provided supportive evidence on the capacity of carnosine to restore or promote the activity of antioxidant enzymes, its ability to inhibit lipid oxidation together with its capacity to inhibit anti-crosslinking between amyloid-β and prion peptides, which altogether encourage the use of carnosine as a preventive and therapeutic approach against PD and AD.…”
Section: Heath Benefitsmentioning
confidence: 99%